Peer-Based Interventions to Improve Self-Efficacy in Patients with Chronic Diseases - Maria Fulgensia Bengu Ndona; Elly Nurachmah; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2025)
Chronic diseases such as heart failure, diabetes, and hypertension require active patient involvement in self-management. Self-efficacy is a key factor that influences the success of self-management among individuals with chronic conditions. This article aims to synthesize current empirical evidence on the effectiveness of peer-based interventions in improving self-efficacy among patients with chronic diseases. This study employed a systematic review approach based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Literature was retrieved from PubMed, ScienceDirect, ProQuest, EBSCOhost, Wiley, and Google Scholar databases. The inclusion criteria were full-text articles in English, with designs such as randomized controlled trials, quasi-experiments, and pilot studies published between 2015 and 2025. Of the 635,062 8 articles identifie the inclusion criteria and were analyzed. The included articles were critically appraised using appropriate tools and independently reviewed for quality and relevance, with data systematically extracted and narratively synthesized due to methodological heterogeneity. All reviewed studies reported a significant increase in self-efficacy following peer-based interventions. These interventions were implemented in various formats, including group training, theory-based peer coaching (eg, Health Belief Model, Health Promotion Model), digital peer support, and nurse-facilitated peer programs. Some studies also demonstrate long-term effects and additional benefits such as improved quality of life, better stress management, and reduced stigma. Peer-based interventions are proven effective in enhancing self-efficacy among patients with chronic diseases and may serve as a complementary strategy in clinical practice and primary health care services.